Graphies, animation and interactivity with flash 4.0 - Mahler, James L (New York Delman Thompson Learning, 2000)
This book covers the features about graphics, animation and interactivity with Flash 4.0. Also covers the intergration of sound into web presentation using Flash.Complete coverage of creation of interactive elements such as buttons,interfaces and ad-banne
Keywords: Computer graphics; Computer animation; Interactive multimedia; Flash (Computer file)